A spiritualitás és a pszichés jóllét összefüggései – A Teisztikus Spiritualitás Változását Mérő Kérdőív (TSOS-HU) magyar adaptációja - SZABÓ-JÁKI, Zsuzsanna; JÁRAY, Márton; SIPOS, Zsolt; TÖRÖK, Gábor Pál; BÓNÉ, Veronika (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
Measurement of the Relationship between Spirituality and Psychological Wellbeing – Hungarian Adaptation of the Theistic Spiritual Outcome Scale (TSOS-HU). This study presents the validation of the TSOS (Theistic Spiritual Outcome Scale) questionnaire measuring changes in theistic spirituality in a Hungarian sample. The measurement of spirituality has become a major topic of scientific interest, especially in the field of health promotion and healthcare. We discuss the relationship between spirituality and wellbeing and present questionnaires on spirituality adapted into Hungarian. In our research, we used the STS and WBI-5 scales in addition to the TSOS-HU, along with demographic data. The average age of participants was 52.9 years. Cronbach’s alpha of the scale is 0.876. Item residual correlations are all above 0.3 (0.370–0.637). Convergent validity of TSOS-HU with STS and WBI-5 was satisfying. Our results revealed that a few items show specific cultural features, and by moving them to a more appropriate subscale, the original factor structure was confirmed. We used principal component analysis (PCA) to see how the items are ordered in our factor structure. The relationships between demographic variables, such as gender, age, level of education, marital status, religious affiliation, and TSOS-HU outcomes, were also analysed. Our results suggest that TSOS-HU is suitable for measuring changes in theistic spirituality in Hungarian samples, and the subscales are also reliable.